2019
DOI: 10.1111/pce.13619
|View full text |Cite
|
Sign up to set email alerts
|

A rice really interesting new gene H2‐type E3 ligase, OsSIRH2‐14, enhances salinity tolerance via ubiquitin/26S proteasome‐mediated degradation of salt‐related proteins

Abstract: Salinity is a deleterious abiotic stress factor that affects growth, productivity, and physiology of crop plants. Strategies for improving salinity tolerance in plants are critical for crop breeding programmes. Here, we characterized the rice (Oryza sativa) really interesting new gene (RING) H2‐type E3 ligase, OsSIRH2‐14 (previously named OsRFPH2‐14), which plays a positive role in salinity tolerance by regulating salt‐related proteins including an HKT‐type Na+ transporter (OsHKT2;1). OsSIRH2‐14 expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 99 publications
(152 reference statements)
0
28
0
Order By: Relevance
“…This is a modified figure from a previous study (Assaha et al, 2017). Regulation of OsHKT2;1 via OsSIRPH2-14 has been reported (Park et al, 2019). XPCs: xylem parenchyma cells which is a K + inward rectifier (Fuchs et al, 2005), exhibited low expression levels in the roots and leaves of transgenic plants.…”
Section: Osrfpv6 Overexpression Plantsmentioning
confidence: 72%
“…This is a modified figure from a previous study (Assaha et al, 2017). Regulation of OsHKT2;1 via OsSIRPH2-14 has been reported (Park et al, 2019). XPCs: xylem parenchyma cells which is a K + inward rectifier (Fuchs et al, 2005), exhibited low expression levels in the roots and leaves of transgenic plants.…”
Section: Osrfpv6 Overexpression Plantsmentioning
confidence: 72%
“…1 a, b), which was not suitable for the crop SSR study. Finally, the NaCl concentration suitable for studying salinity of rapeseed was determined to be 200 mM, which was also widely used in other studies [ 35 39 ]. It might be concluded that 200 mM NaCl could be used as a universal condition for the crop SSR study under hydroponic culture.…”
Section: Discussionmentioning
confidence: 99%
“…OsSIRP1 is a negative regulator of salt tolerance, and its target protein needs to be further studied [49,60]. The microtubule-associated RING finger protein 1 (OsMAR1), an E3 ligase, acts as a negative regulator for salt-stress response through the regulation of the O. sativa chymotrypsin protease inhibitor 2 (OsCPI2), but anther rice RING H2-type E3 ligase, OsSIRH2-14 (previously named OsRFPH2-14), plays a positive role in salinity tolerance by regulating salt-related proteins, including an HKT-type Na+ transporter (OsHKT2; 1) [55,59]. The RING-finger proteins M. esculenta RZF (MeRZF) and SpRing were found to respond to salt stress in cassava and wild tomato, respectively.…”
Section: Ring-finger Proteins Are Involved In Salt and Aluminium Resimentioning
confidence: 99%